Vanlighet som väcker begär - Mattias Frihammar (Kulturella Perspektiv, 2009)
In this article I examine meetings between ordinary people and royals in contemporary Sweden, particularly focusing on the process that makes the royal encounter a special occurrence. Accordingly, I will show how encounters between royals and ordinary people are surrounded by an extraordinary frame, which is established by the ordinary participants, more or less consciously. This frame is then contrasted with assumptions, and experiences, of the ordinariness of the royals. The royal magnificence is accepted as fabricated exhibit — and as such it is nothing but an accepted illusion. But this illusion puts ordinariness on a certain display, making the commonplace and trivial shine in a sensational, royal light.